Comparative Assessment of Selected Fruit Peels on Growth and Yield of Okra (Abelmoschus esculentus (L.) Moench) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study was carried out to examine the effect of selected fruit peels on growth and yield of okra (Abelmoschus esculentus). 10g of ground fruit peels of banana, watermelon, pawpaw, pineapple, plantain, orange was applied to 7 kg of soil and left for 7 days before planting of okra seed.  NPK (15:15:15) serves as positive control while groups without fertilizer served as negative control for the study. Each treatment was replicated five times in polythene bags used as pots and watered every three days. The setup was arranged in Completely Randomized Block Design (CRBD). Plant height and stem girth were measured while number of leaves were also counted from 1 to 8 Week After Planting. The numbers of days to 50% flowering, pod length and pod diameter were also recorded from 1 to 8 Week After Planting. Data pooled in this study were subjected to Analysis of variance (ANOVA) and means with statistically significant difference at p
Keywords: Fruit peels; Okra; Abelmoschus esculentus; Growth; Yield